Comparison of external load during pre-match warm-up among different age categories from the same football professional club - Casamichana, D.; Barba, E.; Nakamura, F. Y.; Agirrezabalaga, O.; Castellano, J. (Kinesiology, 2024)
The aim of the present study was to compare the external load (EL) of the football pre-match warm-up (WU) in absolute terms and as a percentage (%) of the individual match demands. A total of 96 football players from different age categories participated in the study: professional (PRO, n=26), reserve (RES, n=22), under-21 (U21, n=28) and U18 (n=20) teams. Eleven EL variables were obtained through global positioning system devices. The results show that there are differences among teams in total duration, total distance, number of accelerations and decelerations, acceleration load, distance covered at different speed ranges and the maximum velocity, both expressed absolutely and relative to the match demands. The EL of the WU represents a variable percentage depending on a particular variable with respect to the match, ranging from ˜5% for high-speed running or very high-speed running to ˜20% for acceleration-load. The conclusions were: 1) the WU load represents an important part of the EL on players in soccer matches, and 2) the PRO team presented a lower EL in most of the variables, being consistent in both absolute and relative terms to the match demand. The strength and conditioning coaches must be cautious not to cause fatigue in the players while guaranteeing an adequate set-up to dispute the match.